The use of restriction fragment length polymorphisms in prenatal diagnosis of dihydropteridine reductase deficiency. - Dahl, H H (1988)
Using a human dihydropteridine reductase (hDHPR) cDNA probe we have detected two AvaII and one MspI restriction fragment length polymorphisms (RFLPs). We show that these RFLPs are in disequilibrium and calculate that approximately 60% of Caucasians are heterozygous for at least one RFLP. We demonstrate the usefulness of these RFLPs in prenatal diagnosis of DHPR deficiency in one family. This disorder can also be predicted by enzyme assays and we therefore discuss the relative merits of the two methods of prenatal diagnosis.